Aplicativo para gerenciamento de laboratórios didáticos de Química - Ortigara, Jocimar (2015)
The Federal Technological University of Paraná has support rooms to didactical laboratories, such as informatics, electrical and chemistry. These rooms help the laboratories and function as a kind of warehouse and local to the teachers make booking of laboratories to do practical classes and to borrow materials. These places perform activities that are common among laboratories of distinct courses: booking and loans. However, there is much specificity in the items that are borrowed and in the bookings. Thus, it is needed specific software to each of these rooms. In this work it is proposed software as a solution to the support room of chemistry department. Through this software the teachers can be booking the laboratories and materials of their own classes and the laboratory technician can to do a more effective control of material in inventory. The software developed is to web and aims to provide a manner do facilitate the management of loans and reservations. The software development was made using Java as a programming language, Glassfish as web server and PostegresSQL as a data base. The graphical user interface was developed using JavaServer Faces and the customizations were made by Bootstrap.